Ruminal solubility and bioavailability of trace minerals in growing lambs fed varying levels of live yeast with a total mixed ration - Abdelrahman, Mutassim M.; Swelum, Ayman A.; Ba-Awadh, Hani A.; Al-Badwi, Mohammed A.; Alobre, Mohsen M.; Suliman, Gamaleldin M.; Qaid, Mohammed M.; Bahadi, Majdi A.; Al-Owaimer, Abdullah N. (Frontiers in Veterinary Science, 2025)
IntroductionThis study evaluated the effects of yeast supplementation (YS) on trace mineral (TM) concentrations in blood serum, rumen fluid, and meat, as well as on the growth performance of lambs fed a total mixed ration (TMR). In addition, correlations among TM concentrations in different tissues were examined.MethodsA total of 24 healthy, growing lambs were randomly assigned to three groups (n = 8/group): YS0.00, YS1.50, and YS3.00 (0.00, 1.50, and 3.00 g yeast/lamb/day). Feed intake and body weight were monitored every four weeks during the 8-week trial. The samples of blood serum, rumen fluid, and meat were analyzed for Fe, Cu, Zn, I, Se, and Co using ICP-OES.Results and discussionIn the YS3.00 group, yeast supplementation significantly increased overall roughage intake. However, it decreased feed efficiency, indicating that although animals consumed more, nutrient utilization efficiency was altered. The YS1.50 group showed significantly higher serum levels of Mn, Cu, and Se (p < 0.05). Rumen fluid TM concentrations were significantly affected by treatment, with lower values observed in the YS1.50 and YS3.00 groups compared to the YS0.00 group. A similar pattern was observed in meat, with the YS1.50 group showing significantly higher levels of most TMs, except for I and Cu. Strong positive correlations (p < 0.05) were found between rumen and meat TM concentrations for Mn, Fe, Se, and I, as well as between rumen fluid and serum for Fe and Cu. In conclusion, yeast supplementation at 1.50 g/day increased trace mineral concentrations in serum and meat, with the exception of I and Cu, and improved correlations between rumen fluid and meat for Mn, Fe, Se, and I, as well as between rumen fluid and serum, in the growing lambs.